Living Hadis: Tradisi Aqiqah di Kampung Sangkal Kabupaten Bantul dalam Pendekatan Teori Sosiologi Pengetahuan Peter L. Berger - Muhammad, Alaika Abdi; Hartono, Heki (AN NUR: Jurnal Studi Islam, 2024)
This research aimed to reveal the study of living hadith with the theme of the Aqiqah tradition in Sangkal Sewon Bantul Yogyakarta. Methodologically, this research category was field research with a qualitative approach. Research data was obtained through two sources: informant data directly and literature. The research results showed that the aqiqah in Sangkal Village had been practiced by the community for generations. Aqiqah was carried out when the baby was 35 days old, “Selapan” in Javanese terms. This event was attended by all members of the community, both small children and adults. Technically, the implementation of aqiqah in Sangkal village was entirely the responsibility of the women. They would guide the preparations to the running of the event, which included reading prayers and a life history of the Prophet Muhammad through the book Maulid Ad-Dibai. The aqiqah ritual practiced by the people of Sangkal village couldn’t be understood in a social and cultural vacuum. The Prophet's instructions in the hadith regarding aqiqah did not include technical instructions, so that the technical area was filled by the Islamic community with local cultural innovations. The aqiqah tradition in Sangkal village was formed with its uniqueness due to the intersection between traditions and culture in the past with current social realities and as a form of interpretation of the recommendations of religious texts (hadith).